2006
DOI: 10.1139/z06-077
|View full text |Cite
|
Sign up to set email alerts
|

Fledgling production and population trends in Finnish common eiders (Somateria mollissima mollissima) — evidence for density dependence

Abstract: We present a 57-year time series of a common eider, Somateria mollissima mollissima (L., 1758), population from one of the core monitoring areas in the Baltic Sea, the Söderskär bird sanctuary, Gulf of Finland. We applied permutation tests to inspect the relationships between breeding parameters and population density. Of the parameters studied, only fledging rate (during a 34-year period) showed a significant negative relationship with population size, indicating density dependence. Furthermore, the fledging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 28 publications
(29 reference statements)
3
51
0
Order By: Relevance
“…As reported by Hario and Rintala (2006), the fledging rate at Söderskär tended to decrease with time. This was principally an outcome of the extremely low fledging success during the steeply decreasing phase of the population size in 1986-1996, when the per capita fledging rate was 0.052 ± 0.013 (SE).…”
Section: Stressors Of Survival and Reproductionsupporting
confidence: 73%
See 2 more Smart Citations
“…As reported by Hario and Rintala (2006), the fledging rate at Söderskär tended to decrease with time. This was principally an outcome of the extremely low fledging success during the steeply decreasing phase of the population size in 1986-1996, when the per capita fledging rate was 0.052 ± 0.013 (SE).…”
Section: Stressors Of Survival and Reproductionsupporting
confidence: 73%
“…Finally, whatever the causality behind the relatively small range of variation in apparent annual female survival rates, results suggest that female survival is not the main driving force behind the population changes. In a previous study, Hario and Rintala (2006) showed that annual reproductive rate (fledglings/female) at Söderskär was strongly related to population growth rate. The proportion of explainable variance was 61%, whereas the corresponding figure is only 2% in the current survival data (Fig.…”
Section: Effect Of Survival On Population Fluctuationsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in eiders, females rarely have the same clutch size in consecutive years (Erikstad et al 1993), which could be caused by uncontrolled partial predation on Wrst-laid eggs. To take another example, it may prove to be futile to detect density dependence in the fecundity of female eiders (Hario and Rintala 2006), since uncontrolled and potentially elevated partial clutch predation may mask any positive eVect of decreased breeding density on female fecundity. The need to avoid predation of Wrst-laid eggs may even shape the expression of behaviours such as conspeciWc brood parasitism and its counterpart, egg adoption, in eiders (Robertson 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for fluctuating numbers of breeding Common Eiders are not known. ), and Hario & Rintala (2006 have convincingly argued that the decline of the population of Common Eiders on Söderskär, Gulf of Finland, primarily was driven by very low fledging success, while female mortality remained on a low level throughout the period of decline. However, they also argued that productivity was generally depressed all over the core breeding range in the south-western archipelagoes.…”
Section: The West Coastmentioning
confidence: 99%